Prioritizing the teaching methods of ESD using an integrated fuzzy entropy–SAW algorithm (case study: technical and vocational schools). Issue 2 (2nd April 2020) - Ghassami, Fateme; Yousefi, Elham; Salehi, Esmail
Abstract: The current environmental crisis has mainly a human-induced origin. In this regard, technical and vocational (T&V) graduates have an important role in the optimal use of environment and resources. Therefore, this research intends to find the best teaching method of education for sustainable development (ESD) in order to improve the behavior of those graduates toward the environment. For this purpose, the fuzzy entropy method was used to introduce and weight the sustainable development competency criteria of the T&V graduates. Then, the teaching methods were prioritized by applying a fuzzy Simple Additive Weighted (SAW) model. According to the results of the present paper, performance-based learning was the most appropriate method of ESD.